Study of equilibrium, thermodynamic and kinetic nickel adsorption by kaolinite, bentonite and local clay minerals - Mohammed Malik Yassen ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Three clay minerals Kaolinite(K), Bentonite(B) and local clay(L)were used to study their efficiency on nickel(Ni) adsorption by isothermal equilibrium reactions which consist langumer, Freundlich and temkin models with linear and non-linear forms. Data adsorption was submitted to thermodynamic models to measure the standard free energy(ΔG˚), change of enthalpy(ΔH˚) and change in entropy(ΔS˚). Another experiments was conducted to understand the nickel absorption kinetics. Eight models were applying Elovich , Fractional power , zero order , first order , pseudo first order , second order , pseudo second order and Intraparticle diffusion. The clay minerals took on the following order in efficiency increasing of Nickel adsorption: B >K > L . And local clay show more efficiency in removing with increasing of added Nickel concentration. Freundlich model show superiority in description of nickel adsorption a kaolinite and bentonite minerals comparison with another models. Non-linear from took on best representation comparison with linear form through correlation coefficient (R2) and standard deviation percentage(MPSD), whereas langumer model in linear form was better for local minerals. ( ΔG˚) result show the spontaneity and feasibility of the adsorption process to kaolinite and bentonite inverse the local mineral which show the non-spontaneity process. (ΔH˚) values indicate to the endothermic nature of nickel process with the three minerals. (ΔS˚) values show to the increase the random of nickel absorption with minerals. pseudo second order kinetic model took on the best representation in determination of the rate of nickel absorption at kaolinite and bentonite minerals surface and rather for the local clay.